Improvement of Near Vision for Low Vision Patients in National Eye Healthcare Center Cicendo Eye Hospital 2010-2011 - Muhammadnur Rachim Enoch; Ine Renata Musa; Titing Nurhayati (Faculty of Medicine Universitas Padjadjaran, 2014)
Background: “Low vision” is a term used refer to a person having a visual acuity of less than 6/18 (20/60) to light perception (LP). People with low vision can still be treated to perceive or see objects, although several limitations occur. Treatments for people with low vision include either optical or non-optical devices. This research aims to reveal visual acuity for near vision that can serve as corrective benchmark after devices for near vision are given.Methods: This is a retrospective descriptive research, using medical records from the National Eye Healthcare Center, Cicendo Eye Hospital, for the period of August 2010–September 2011 as the subject of the research. Approximately 475 patients were listed, 263 female and 212 male. The number of patients with low vision given with corrective device for near vision were 81 patients.Results: The result showed that visual acuity was corrected after corrective devices for near vision with the size of 1–10 M were given.Conclusions: The highest of overall corrections or improvements for near vision are the one under the category of “severe visual impairment”.Key words: low vision, optical devices, visual acuity Peningkatan Penglihatan Jarak Dekat Pada Penderita“ Low Vision” di RS Mata Nasional Cicendo 2010–2011 LatarBelakang: